Research note: The effect of different indexation scenarios on child poverty in the UK - Paola De Agostini; Iva Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2015)
Using the tax-benefit microsimulation model EUROMOD and Family Resources Survey, we investigate what would have happened to child poverty in the UK in the periods 2010/11-2015/16 and 2015/16-2020/21 under a range of different indexation scenarios of children's benefits. We find that between 2010/11 and 2015/16 both the relative and absolute child poverty rates would have been lower if children's benefits were uprated by RPI or if the government had introduced the Child Tax Credit uprating package it promised in 2010. Uprating children's benefits up to 2020/21 as announced by the government in the Autumn Financial Statement in 2014 would result in real benefit cuts and increase in child poverty. However, triple lock indexation of children's benefits would sustain their real value and would reduce child poverty rates substantially.
Keywords: H23; H53; I38; 330; benefit indexation; child poverty; UK; microsimulation